2022
DOI: 10.19171/uefad.1110455
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlerin Teknolojik Pedagojik Alan Bilgisi ve Eğitim Bilişim Ağı’nı (EBA) Kullanma Öz-Yeterlikleri

Abstract: This study attempted to explore the teachers’ self-efficacy perceptions of Education Informatics Network (EIN) use and identify whether their self-efficacy perception of Technological Pedagogical Content Knowledge (TPCK) was a predictor of their self-efficacy perceptions levels of Education Informatics Network use. This study also sought to whether teachers’ self-efficacy perceptions of the Education Informatics Network use differ according to age, professional experience, school type, level of computer use, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Considering the education level variable, it is seen that TPACK efficacy levels of mathematics teachers with bachelor's degree are lower than those with master's degree and doctoral degree. These findings are in parallel with the results of Boran & Genç (2022) and Tiryaki & Hali (2022) studies and in this context, it is concluded that the TPACK competence levels of mathematics teachers increase as the level of education they study increases.…”
Section: Conclusion and Suggestionssupporting
confidence: 85%
“…Considering the education level variable, it is seen that TPACK efficacy levels of mathematics teachers with bachelor's degree are lower than those with master's degree and doctoral degree. These findings are in parallel with the results of Boran & Genç (2022) and Tiryaki & Hali (2022) studies and in this context, it is concluded that the TPACK competence levels of mathematics teachers increase as the level of education they study increases.…”
Section: Conclusion and Suggestionssupporting
confidence: 85%